INDEPENDENCE AND INTERDEPENDENCE: MULTIDIMENSIONALITY OF FINNISH YOUTH’S EXPERIENCES OF TRUST IN NEWS ONLINE AND VIA SOCIAL MEDIA - Horowitz, Minna; Matikainen, Janne (AoIR Selected Papers of Internet Research, 2021)
Young people’s relationship with the news has been a cause of concern, especially due to the role of social media as a central component of their lives, often seen as a prominent cause of declining trust in the news. This proposal features some of the results of a multi-method, interdisciplinary study of the University of Helsinki (2019-2021) that examines how Finnish audiences view the power of traditional news media and social media. The project understands trust as a four-dimensional concept: generalized trust in the media, trust in specific sources, trust in terms of specific issues, and trust determined by one’s individual disposition. Based on the results of two general surveys in Spring 2019 and Spring 2020, a survey focused on young people (18-29-year-olds), three focus group interviews, as well as a three-day online discussion of 30 participants of the same age group in Fall 2020, we analyze how young people and experience the trust in news sources online. We also discuss how the pandemic has shaped their experiences. While the most defining characteristic of Finnish audiences is a combination of both basic trust and critical approaches toward news, this is markedly true for young people. At the same time, our findings do not confirm the worst fears of moral panic about growing distrust and news avoidance by young people. Rather, they suggest a combination of independence and interdependence by young people, of both legacy news media and online and social media sources.